2017
DOI: 10.1097/mpa.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

A Report of 320 Cases of Childhood Pancreatitis

Abstract: There was 7-fold increase in number of hospitalization due to pancreatitis over the years. Progression of AP to ARP/CP was noted in 21.5% and ARP to CP in 22%. Thus, a subset of pancreatitis seems to be a continuum of acute to ARP and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
8
31
0
Order By: Relevance
“…In this study, we found that in-hospital mortality rate of AP ranged from 0.35% to 4.2% in the last 14 years (Table 3), without a significant trend or gender difference. The most common risk factor or comorbidity was systemic disease, which was consistent with previous studies (5,11–13).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that in-hospital mortality rate of AP ranged from 0.35% to 4.2% in the last 14 years (Table 3), without a significant trend or gender difference. The most common risk factor or comorbidity was systemic disease, which was consistent with previous studies (5,11–13).…”
Section: Discussionsupporting
confidence: 91%
“…Bolia et al [ 24 ] reported that 38% of PAP patients developed PCs, and half of them required drainage. Poddar et al [ 1 ] retrospectively reviewed 320 pediatric pancreatitis patients, including 160 patients with AP, 67 with acute recurrent pancreatitis, and 93 with chronic pancreatitis, and found that 60 patients (18.7%) developed PCs. History of abdominal trauma was documented in 27.2% to 100% of children with PC, but whether traumatic or nontraumatic PCs are more likely to resolve spontaneously is conflicting [ 21 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…History of abdominal trauma was documented in 27.2% to 100% of children with PC, but whether traumatic or nontraumatic PCs are more likely to resolve spontaneously is conflicting [ 21 22 23 24 ]. Putting together nine studies mentioning pediatric PCs, a total of 212 cases were reported [ 1 6 21 22 23 24 25 26 27 ]. Among the 152 cases with predisposing factor reported, 112 (73.7%) had a history of abdominal trauma and 24 (15.8%) were idiopathic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations